Experimental Observations of Heat-Assisted Boycott Effect in Trapezoidal Enclosures - Fernando Apaz; Christian F. Ihle (Applied Sciences)
The present study examined the influence of controlled heat injection on the sedimentation of fine particles in a trapezoidal container, aiming to explore the combined effects of the Boycott effect and convection induced by heating. The experimental design incorporates varying initial particle concentrations (1500 ppm and 3000 ppm) and heat injection levels (0 W, 4.5 W, and 9 W imposed power) to analyze sedimentation dynamics, focusing on concentration distribution patterns and clear water production. The findings reveal complex interactions between heat injection and particle concentration. At 1500 ppm, heat injection shows minimal impact on sedimentation due to particle resuspension. However, at 3000 ppm, particularly with a 9 W heat injection, the sedimentation performance improves significantly during the early stages of the process, achieving an average sedimentation rate approximately 40 % higher than without heat injection and an average clear water generation rate nearly four times greater. These clear water generation rates were determined considering water with particle concentrations below 20 % of the initial concentration (300 ppm for 1500 ppm and 600 ppm for 3000 ppm). A further analysis of the column and row data reveals stratification patterns influenced by heat injection, characterized by distinct horizontal and vertical layers. Additionally, the results suggest that wall temperature distributions are largely unaffected by the initial particle concentration, while clear water production and sedimentation efficiency are highly dependent on heat levels and initial particle density. These results highlight the potential of heat-enhanced sedimentation to improve separation processes in industrial systems. Specifically, they provide valuable insights for optimizing the design and efficiency of lamella settlers, commonly used in water treatment and other particulate separation applications. Future studies will explore the combined use of coagulants and flocculants and the application of these findings to real mixtures, such as mine water or wastewater, to further validate and expand their industrial applicability.